Subpopulações de Linfócitos B e Parâmetros Imunes na Evolução do Infarto Agudo do Miocárdio com Supradesnivelamento do Segmento ST - Casarotti, Ana Carolina Carneiro Aguirre [UNIFESP] (2019)
Introduction: Early reperfusion is universally recommended for the treatment of patients with ST segment elevation myocardial infarction (STEMI). However, despite early pharmacological thrombolysis or primary percutaneous intervention, some patients still present large amounts of myocardial necrosis and significant impairment of ventricular function. Objetive: This study aimed to evaluate the role of inflammatory responses mediated by lymphocytes in the infarcted mass and ventricular remodeling after STEMI. Methods: Blood samples were collected in subjects with STEMI (n=120) in the first (D1) and 30th day (D30). All patients were submitted to pharmacological thrombolysis in the first 6 hours followed by coronary angiogram and percutaneous intervention if necessary in the first 24h of STEMI (pharmacoinvasive strategy). Flow Cytometry was used to quantify B and T lymphocytes subtypes followed by ELISPOT assay to determine spontaneously secreted IgM by B1 cells. Total plasma IgM and cytokine titers were also measured by ELISA. Cardiac MRI in the 30th day was used to estimate the myocardial fibrosis mass and left ventricular function. Results: A decrease in B lymphocytes subtypes count (cells/ml) was observed in D30 compared to D1 (all p<0.001), and for TCD4+ (p=0.049), but not for TCD8+ (p=0,097). Higher IgM concentration was observed in D30 (p<0.001) and it was mainly related to B1 cells (rho=0.227; p=0.014). In addition, the frequency of B1CD11b+ cells in D1 was positively associated with the infarcted mass (rho=0.184; p=0.045). There was an increase in interleukin (IL) 4 and IL10 titers at D30 (p=0.013 and p<0.001, respectively), while IL-6 titers remained unchanged (p=0.31). Samples obtained in D1 showed that IL6 titers were associated with the infarcted mass (rho=0.414, p<0.001) and also inversely related to left ventricular ejection fraction (rho=-0.38; p<0.001). Conclusion: Despite early reperfusion, final infarcted mass at D30 and ventricular remodeling seem partially related to the inflammatory responses.